Study the effect of oxazepine derivatives of alkaline phosphatase in normal persons sera (Journal of the College of Basic Education, 2022)
The inhibitory effect of new organic compound which is derivative of oxazepine on the activity of alkaline phosphatase in normal persons serum have been studied This compound was :2 ( p-toyl) 3 – (2- traizole ) -2,3 dihydro {1,3} – oxazepine – 4,7 dione The percentage of inhibition caused by oxazepine derivative was to be arranged between 22.5 – 69 % The result from line weaver – burk plot indicated that the inhibition was competitive which maximum velocity vmaxwhile Micheal menten constant Km is decreased in presence of inhibitor 9 m mol/L while the value of Km without inhibitoris 10 m mol/L .synthesis new 1,3 oxazepine 4-7 dion derivatives which are expected to have biological activity which are most active anticonvulsant.